The Invisibility of Regional Politics on Television - Georgia Gioltzidou; Foteini Gioltzidou (Central European Journal of Communication, 2026)
Regional media play a crucial role in democratic journalism by fostering local accountability and promoting public debate. Yet inequalities between central and peripheral areas may shape the visibility of regional political issues. This study analyzes political news coverage in the main evening bulletins of ERT3, a Greek public television station. Drawing on content analysis, it examines airtime allocation, thematic focus (local, national, and international politics), and story placement within the news agenda. The findings indicate limited visibility of local political affairs and a clear imbalance in favor of central political actors. These results shed light on the structural constraints facing regional broadcasters and contribute to broader debates on media centralization and the democratic role of regional journalism.